UPAYA PENINGKATAN KESEHATAN MELALUI KEGIATAN SENAM DI BALAI DESA PADANG TUALANG KABUPATEN LANGKAT - Amru Prabowo Lubis; Fadilah, Sylva Qamara Nur; Sari, Anggi Novita; Nabilla Tawaqal Ainy Kusuma; Ulfiyah Az-zahra Dahlan; Siregar, Zahwatul Hasanah; Susilawati, Susilawati (Universitas Mataram, 2024)
Efforts to improve health and physical fitness can be interpreted as efforts to maintain and improve physical condition so that it remains optimal and able to carry out daily activities well. Physical fitness includes several aspects, such as muscle strength, heart and lung endurance, flexibility, and a much healthier body composition. This research discusses the implementation of physical fitness activities in Padang Tualang Village as part of the Community Service Program (KKN) and Field Learning Practices (PBL) by students at the Faculty of Public Health, UIN North Sumatra. This activity aims to increase public knowledge and awareness, especially PKK mothers and the elderly, regarding the importance of physical activity for health. The methods used include delivering instructional material, demonstrating gymnastic movements, and using audio-visual media. The results of the activity show that exercise not only improves physical fitness, but also strengthens people's understanding of the importance of physical activity in maintaining health. The conclusion of this research is that the physical fitness activities carried out in Padang Tualang Village showed positive results in improving the health and fitness of the community.